ISOLASI, ENUMERASI, DAN KARAKTERISASI BAKTERI PELARUT FOSFAT (BPF) INDIGENUS TANAH DESA KEBUNAN SUMENEP SEBAGAI AGEN PUPUK HAYATI ORGANIK - Hefdiyah, H.; Ali, Mahrus; Utami, Vita Kurnia (LP4MK STKIP PGRI Lubuklinggau, 2023)
Phosphate Solubilizing Bacteria (PSB) are known that have important role to improve plant phosphate uptake as biofertilizer. These Microorganism hold potential to promote organic agriculture as eco friendly and efficiency. This study aims to isolate, enumerate and characterize indigenous PSB from Kebunan Village soil as the organic biofertilizer agent. Isolation and enumeration were carried out using the spread plate method on PCA media for enumeration of the total bacteria and Pikovskaya media (PKV) and NBRIP for BPF selection and enumeration. characterization includes observing the morphological colonies and cells. These experimental studies found that the soil pH was 6.5, the temperature range was 28-35 °C, the total P content was from 0.59 to 1.09 and the dissolved phosphate content sequentially from the smallest is 0.53 (KB2), 29.41 (KB1), 60.45 (KB3). The total abundance of bacteria at 3 different locations showed variations between 1.97 x 106 to 287 x 106. The highest abundance of BPF reached 5.45 x 106 cfu/g was in the watershed which had the lowest available P content. Total 7 isolates of BPF were successfully isolated and characterized with different colony characters and cell shapes. The selected BPF isolates were dominated by Gram-positive bacilli.